Plant behaviour under combined stress: tomato responses to combined salinity and pathogen stress. (19th January 2018) - Bai, Yuling; Kissoudis, Christos; Yan, Zhe; Visser, Richard G.F.; van der Linden, Gerard
Summary: Crop plants are subjected to a variety of stresses during their lifecycle, including abiotic stress factors such as salinity and biotic stress factors such as pathogens. Plants have developed a multitude of defense and adaptation responses to these stress factors. In the field, different stress factors mostly occur concurrently resulting in a new state of stress, the combined stress. There is evidence that plant resistance to pathogens can be attenuated or enhanced by abiotic stress factors. With stress tolerance research being mostly focused on plant responses to individual stresses, the understanding of a plant's ability to adapt to combined stresses is limited. In the last few years, we studied powdery mildew resistance under salt stress conditions in the model crop plant tomato with the aim to understand the requirements to achieve plant resilience to a wider array of combined abiotic and biotic stress combinations. We uncovered specific responses of tomato plants to combined salinity‐pathogen stress, which varied with salinity intensity and plant resistance genes. Moreover, hormones, with their complex regulation and cross‐talk, were shown to play a key role in the adaptation of tomato plants to the combined stress. In this review, we attempt to understand the complexity of plant responses to abiotic and biotic stress combinations, with a focus on tomato responses (genetic control and cross‐talk of signaling pathways) to combined salinity and pathogen stresses. Further, we provide recommendations on how to design novel strategies for breeding crops with a sustained performance under diverse environmental conditions. Significance Statement: This manuscript addresses the particularly interesting and important topic of plant responses to combined stresses, an area of research that is still poorly understood. Combined stresses occur in field conditions and have been described to affect crop development and ultimately yield. After reviewing the complexity of plant responses to combined abiotic and biotic stresses, we propose requirements and strategies for consideration in plant breeding programs in order to maintain high crop performances.